FAKTOR â FAKTOR PENGHAMBAT KEBERHASILAN MEDIASI PERCERAIAN DI PENGADILAN AGAMA KARANGANYAR - Suhangga, Artha; Wibowo, Anthony; Rianto, Agus (PARENTAL, 2013)
This research aimed to find out the factors inhibiting the successful divorce mediation in Karanganyar Religion Court, so that a solution can be found to maximize the successful mediation. After the enactment of Supreme Courtâs Regulation Number 1 of 2008 about Mediation Process in Trial, mediation has become an important series of entire case management process in Religion Court. However, in Karanganyar Religion Court only 3 cases have been successfully mediated out of 429 cases mediated during 2011. This study was a normative descriptive research. The data of research included primary and secondary data. Meanwhile, techniques of collecting data used were library study and interview. The result of research showed that mediation in Karanganyar Court encountered such constraints as husbandâs/wifeâs determination, less maximum effort of the judge in mediating, the presence of suit accumulation, mediation arising from the parties in case but from the judge, low number of mediator personnel, low education of the parties in dispute, high number of cases incoming, and low participation among the parties in dispute. The benefits of research were to give representation on the problem studied and to be used as the input to any related parties.